Battle and Bloodshed : the Medieval World at War. - Bleach, Lorna (Cambridge Scholars Publishing, 2013)
This collection of articles is the result of an interdisciplinary Medieval Studies conference held at the University of Sheffield in 2009. Brutality and aggression were a stark reality of everyday life in the Middle Ages; from individual rebellions through family feuds to epic wars, a history of medieval warfare could easily be read as a history of medieval violence. This volume goes beyond such an analysis by illustrating just how pervasive the nature of war could be, influencing not only me ...